Outcome of Trial of Labour with Previous One Ceasarean Section (Medical Forum Monthly, 2024)
Objective: To determine fetomaternal outcome of trial of labour in patients with Previous One Ceasarean Section.Study Design: Descriptive Case Series based on hospital data.Place and Duration of Study: This study was conducted at the Obstetrics and Gynaecology Department, Shahina Jamil Teaching Hospital Abbottabad, from February 2013 to August 2013.Materials and Methods: Total 100 cases were selected. During trial of labour, patients were closely monitored by vital signs, fetal cardiac activity, lower abdominal pain and tenderness, fetal distress.Data was collected on proforma and written informed consent was taken on consent form. The permission was taken for hospital committee and the data was analyzed for results.Results: 61 cases (61 %) had successful vaginal delivery while 39 (39 %) patients ended up with repeat emergency caesarean section after failed trial of labour. Out of 61 vaginal deliveries, 53 cases (86.88%) belong to age group 20-30 yrs, while 8 cases (13.12%) were between 31-40 years. Out of 39 cases, 36 cases (92.30 %) belonged to age group of 20-30 years while 3 cases (7.7 %) had age between 31 to 40 years. Distribution of cases, according to fetal distress in patients with emergency caesarean section shows that out of 39 cases, 12 cases (30.70 %) developed fetal distress and 27 cases (69.23 %) were without fetal distress.Conclusion: This study shows that patients with Previous one caesarean section for non-recurrent indication can be successfully delivered vaginally.